2019
DOI: 10.1109/jestpe.2019.2893591
|View full text |Cite
|
Sign up to set email alerts
|

A High-Frequency Inverter for Variable-Load Operation

Abstract: Inverters operating at high frequency (HF, 3-30MHz) are important to numerous industrial and commercial applications such as induction heating, plasma generation, and wireless power transfer. A major challenge in these applications is that the load impedance can vary dynamically in both real and complex components over a wide range, making it difficult to maintain high-efficiency soft-switched operation. The constraints that a variable load impedance place on high frequency inverter design results in systems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Re-introduction of the series diodes in the CSRI topology could relax the timing requirements in applications where robustness of the control is desired, at the expense of increased losses and component count [24,27]. Alternatively, using a microcontroller with a high-resolution PWM architecture to create the driving signals, as done in, for example, [35] and [36], would likely also enable operation closer to the breakdown voltage of the switches. The tradeoff in this approach is that if the system is extended to closed loop control, FIGURE 14 Calorimetric measurement of the efficiency of the CSRI power module at varying output power the FPGA is not available for the implementation of a control algorithm with fast real time response.…”
Section: Resonant Operationmentioning
confidence: 99%
“…Re-introduction of the series diodes in the CSRI topology could relax the timing requirements in applications where robustness of the control is desired, at the expense of increased losses and component count [24,27]. Alternatively, using a microcontroller with a high-resolution PWM architecture to create the driving signals, as done in, for example, [35] and [36], would likely also enable operation closer to the breakdown voltage of the switches. The tradeoff in this approach is that if the system is extended to closed loop control, FIGURE 14 Calorimetric measurement of the efficiency of the CSRI power module at varying output power the FPGA is not available for the implementation of a control algorithm with fast real time response.…”
Section: Resonant Operationmentioning
confidence: 99%
“…2 [8], such that soft switching can be achieved with a variable resistive/inductive load. Other variable-load singleswitch inverters such as class E or class φ 2 inverters (e.g., [4]) can also be used, though the variable-load class D inverter has a relatively superior switch utilization [11], so may be preferred at frequencies and voltage levels at which its highside device can be effectively driven. It is important to note that in many switched-mode inverters two dominant loss mechanisms that can limit achievable performance include switch conduction losses and output capacitor losses.…”
Section: Techniques For Output Power Controlmentioning
confidence: 99%
“…This can be achieved by utilizing dynamically adjustable networks (e.g., a TMN) to dynamically change the loading of the inverters (e.g., [5], [30]). Alternatively, the system can utilize dynamic interactions between a number of inverters to achieve output power control while maintaining acceptable inverter loading for high efficiency operation [11], [31]. A further possible approach is to turn on and off individual inverter or power amplifier subsystems to cause load modulation of active units (and reduce power loss otherwise associated with inactive units), e.g., [32].…”
Section: Structural Modulationmentioning
confidence: 99%
“…Although this approach allows a high-efficiency operation over a wide load range, the output voltage range of typical RF dc-dc converters is limited [2], [17]. However, it has been shown that the flexibility of the converters can be increased by additional circuit effort [13], [19], [20].…”
Section: Introductionmentioning
confidence: 99%